PESANTREN AT-TAUBAH DI LEMBAGA PEMASYARAKATAN KELAS II B CIANJUR - Ta’rif Ta’rif; Husen Hasan Basri (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2015)
AbstractA displacement of the imprisonment to the penitentiary replaces the term of prisoner becomes penitentiary-developed resident. The penitentiary system is oriented on the efforts of preservation, development, education and up-building. One of the development forms for the developed resident is the development and up-building on mental and religious education. The penitentiary of Class II B Cianjur conducts at-Taubah boarding school. Where and what kind of position for at-Taubah Boarding School at the Penitentiary and how the religious education is conducted. Through qualitative method, it is found that at-Taubah boarding school is established by one of the developed residents and the Penitentiary itself. It concluded that at-Taubah boarding school constitutes a therapy boarding school and religious education in the frame of establishment of the Moslem personality. AbstrakPergeseran kepenjaraan kepada lembaga pemasyarakatan menggantikan sebutan narapidana menjadi warga binaan pemasyarakatan. Sistem pemasyarakatan berorientasi kepada usaha perawatan, pembinaan, pendidikan, dan bimbingan. Salah satu bentuk pembinaan bagi warga binaan adalah pembinaan dan bimbingan mental kerohanian dan pendidikan agama. Lapas Kelas II B Cianjur menyelenggarakan pesantren at-Taubah. Dimana apa posisi pesantren at-Taubah di Lapas dan bagaimana penyelenggaraan pendidikan agama. Melalui metode kualitatif, ditemukan bahwa pesantren at-Taubah didirikan oleh salah satu warga binaan dan pihak Lapas. Pesantren at-Taubah terpadu dengan pembinaan di Lapas. Disimpulkan bahwa pesantren at-Taubah merupakan pesantren terapi dan pendidikan keagamaan dalam rangka pembentukan kepribadian muslim